Detection of Francisellaceae and the differentiation of main European F. tularensis ssp. holarctica strains (Clades) by new designed qPCR assays - Kristin Köppen; Kerstin Rydzewski; Julia Zajac; Marwah Al-Senwi; Sema Evcimen; Darius Schulze; Daniela Jacob; Klaus Heuner (BMC Microbiology)
Abstract Background The zoonotic and highly infectious pathogen Francisella tularensis is the etiological agent of tularemia. Tularemia in humans is mainly caused by F. tularensis subspecies tularensis and holarctica, but Francisella species like F. novicida, F. philomiragia, F. hispaniensis and others are known to cause tularemia-like infections in immunocompromised humans. In addition to these Francisella species, further genera of the family Francisellaceae have been described, such as Allofrancisella, Parafrancisella and Pseudofrancisella, but less is known about the distribution and putative virulence of these genera. The methods currently available were not made for a fast and easy detection of all these strains and genera of Francisellaceae. Results We developed a multiplex quantitative real-time PCR assay that can accurately detect all genera of Francisellaceae, including Francisella, Francisella-like endosymbionts, Allofrancisella, Parafrancisella and Pseudofrancisella. In addition, we developed a qPCR assay to differentiate the major clades (B.4, B.6 and B.12 [B.71 and B.72]) of F. tularensis ssp. holarctica strains. Both primer sets were shown to work on isolated DNA out of human and tick samples. Conclusion Since the developed qPCRs are able to detect all genera of Francisellaceae tested, an easy and fast identification of opportunistic Francisella strains causing tularemia-like symptoms in humans or animals is possible now. The application of these qPCR assays will thus improve the capability for clinical diagnostics and molecular typing during epidemiological investigations.